PERBAIKAN CITRA DOKUMEN TERDEGRADASI DENGAN METODE PENGATURAN KONTRAS DAN OTSU THRESHOLD - Wirawan, Bima Muhammad; Rasmana, Susijanto Tri; Triwidyastuti, Yosefine (Journal of Control and Network Systems (JCONES), 2017)
Contrast stretching will help the thresholding to produce binary image with a better quality. Otsu threshold has very important disadvantage, in the image that has not good contrast, The Otsu method is difficult in finding the optimal threshold value to discriminate between foreground and background. Contrast stretching method is useful to stretch the contrast, so that the contrast in the image quality can be more evenly distributed simultaneously, and then can improve the appearance of grayscale images to processed into binary image. The system has an average success of 86.6907%, based on the value of the F-Measure. The output of this system is considered very good and can be used for other processes or for other purposes..keyword: contrast, images, document, threshold, grayscale, binary.